Friends, Foes, and Future Directions U.S. Partnerships in a Turbulent World: Strategic Rethink - Binnendijk, Hans (RAND Corporation, 2016)
Report evaluates strategies for dealing with U.S. partners and adversaries in Europe, Asia, and the Middle East in a time of diminishing defense budgets and American public preference for a domestic focus. The three proposed strategies are to be more assertive, to be more collaborative, or to retrench from international commitments. Each strategy is constrained and a balance will need to be struck among them that varies from region to region.